Creep Fracture Mechanisms and Maps in Aisi Type 316 Austenitic Stainless Steels from Distinct Origins - Monteiro,Sergio Neves (2017)
Two distinct AISI type 316 stainless steels, of Brazilian and Swedish origins, were compared regarding their creep fracture mechanisms at 600, 700 and 800°C. The possible mechanisms associated with the creep fracture strength were identified by means of fracture maps proposed either by Ashby and collaborators or by Miller and Langdon. Experimental creep results were consistent with the general Ashby and collaborators map for face centered cubic alloys. By contrast, the two different 316 steel displayed significant differences in the model-based map of Miller and Langdon. In the present work, changes in the maps frontier are proposed as well as the introduction of a new field in the map related to grain boundary precipitation. These propositions allowed the Miller and Langdon map to be coherent with the experimental creep fracture results of both 316 stainless steels.